Formation of Coelenteramine from 2‐Peroxycoelenterazine in the Ca2+‐Binding Photoprotein Aequorin. (12th January 2022) - Inouye, Satoshi; Nakamura, Mitsuhiro; Hosoya, Takamitsu
Abstract: Aequorin consists of apoprotein (apoAequorin) and ( S )‐2‐peroxycoelenterazine (CTZ‐OOH) and is considered to be a transient‐state complex of an enzyme (apoAequorin) and a substrate (coelenterazine and molecular oxygen) in the enzymatic reaction. The degradation process of CTZ‐OOH in aequorin was characterized under various conditions of protein denaturation. By acid treatment, the major product from CTZ‐OOH was coelenteramine (CTM), but not coelenteramide (CTMD), and no significant luminescence was observed. The counterparts of CTM from CTZ‐OOH were identified as 4‐hydroxyphenylpyruvic acid (4HPPA) and 4‐hydroxyphenylacetic acid (4HPAA) by liquid chromatography/electrospray ionization–time‐of‐flight mass spectrometry (LC/ESI‐TOF‐MS). In the luminescence reaction of aequorin with Ca 2+, similar amounts of 4HPPA and 4HPAA were detected, indicating that CTM is formed by two pathways from CTZ‐OOH through dioxetanone anion and not by hydrolysis from CTMD. Abstract : The formation of coelenteramine (CTM) from ( S )‐2‐peroxycoelenterazine (CTZ‐OOH) in aequorin was investigated under protein denaturing conditions. Under acidic conditions, 4‐hydroxyphenylpyruvic acid (4HPPA) and 4‐hydroxyphenylacetic acid were identified as the counterparts of CTM by LC/ESI‐TOF‐MS analysis. This study shows for the first time that CTM and 4HPPA can be generated from CTZ‐OOH without light emission.